Basic flow of phosphorous in brackishwater - Baldevarona, Rodolfo B.
The study was conducted to determine the influence of fertilizer (18-46-0) on inorganic phosphorus in water; total phosphorus in lab-lab layer, soil and bangus yield to relate inorganic phosphorus with certain water physico-chemical properties, lab-lab layer and soil; and, to infer from the results the possible flow of phosphorus in relation to bangus production, Nine earthen ponds were sed comprising three treatments ( A-zero kg/ha; B - 11 kg/ha; and C - 22 kg/ha 18-46-0 fertilizer) at three replicates.Bangus fingerlings were stocked at 3,000/ha and cultured for 120 days by lab-lab method. Fertilization considerably increased phosphorus concentration of water which was significantly correlated with nitrate-nitrogen (r = -0.364; α = 0.01). Water pH was significantly correlated with alkalinity ( r = 0.6129; = 0.01).Total lab-lab and soil phosphorus were significantly correlated ( r = 0.477; α = 0.05). ANOVA of bangus yield revealed no significant difference among treatments, although fish mean weight, growth rate and production increased with fertilization rates. Finfishes contained 2.22% P to 2.54% P. Total phosphorus in pond soils (5-cm depth) increased four to six-folds after the experiment. The available phosphorus was utilized by primary producers and lab-lab community which were fed pon by the fish by filter feeding in the water column and browsing at the pond bottom. Whatever amount not taken by the fish remained in the water column, lab-lab layer, and soil. Lab-lab layer had the greatest concentration of total phosphorus compared with those in the water column and 2-cm layer of pond soil.